SEIR MODEL SIMULATION WITH PART OF INFECTED MOSQUITO EGGS - Mangobi, James Uriel Livingstone (PATTIMURA UNIVERSITY, 2023)
Dengue hemorrhagic fever (DHF) is an acute febrile disease caused by the dengue virus, which is transmitted by various species of Aedes mosquitoes. The SEIR model is a mathematical model for studying the spread of dengue fever. In this model, it is assumed that some mosquito eggs have been infected because infected mosquitoes can transmit the virus to their eggs. The main vector of this disease is the Aedes albopictus mosquito. Analysis was carried out to assess the stability of the equilibrium point, and numerical simulations were carried out to see changes in population numbers due to changes in parameter values. A disease-free equilibrium (DFE) point, which is stable given the basic reproductive number . An endemic point whose stability is guaranteed if the value . The numerical simulations show that an increasing mosquito mortality rate decreases the number of exposed, susceptible humans. Furthermore, an increase in the average bite of an infected mosquito will increase the number of exposed, susceptible humans. For the mosquito population, increasing mosquitoes’ mortality rate will decrease the number of exposed, susceptible mosquitoes. Finally, an increase in the average bite of an infected mosquito will increase the number of exposed, susceptible mosquitoes.